UNVEILING EMOTIONAL MESSAGES: AN ANALYSIS OF HALLIDAY'S METAFUNCTIONS IN THE MESSENGER BY LINKIN PARK - Nor Laeli Komariyah; Agnes Widyaningrum; Dewi Puspitasari (LINGUAMEDIA Journal, 2025)
This study explores the song The Messenger by Linkin Park through the lens of Halliday's Language Metafunction theory, aiming to uncover its underlying ideology and emotional messages. Utilizing qualitative and descriptive research methods, the analysis focuses on the song's lyrics, examining their Ideational, Interpersonal, and Textual meanings. The results highlight the prominence of specific language processes, including Mental, Material, and Relational, which collectively convey powerful themes of love, hope, and resilience. The Ideational metafunction reveals how the song portrays love as a vital force in overcoming life's adversities, while the Interpersonal metafunction demonstrates how empathetic and supportive language fosters a connection between the singer and the audience. Additionally, the Textual metafunction underscores the structured and cohesive organization of the lyrics, amplifying their emotional impact. The study concludes that The Messenger embodies an ideology that positions love as a source of emotional empowerment and solidarity, providing listeners with comfort and motivation during challenging times. This research contributes to understanding how music serves as a cultural and linguistic artifact that facilitates shared emotional experiences and reinforces resilience.